Reusability of model components for environmental simulation – Case studies for integrated coastal zone management. (June 2015) - de Kok, Jean-Luc; Engelen, Guy; Maes, Joachim
Abstract: Model constructs in environmental models are seldom reused beyond the project lifetime or in other modelling studies. A library of reusable model components could facilitate the maintenance of existing models and make the design of new models more efficient. Although component-based design is the common standard in software engineering and manufacturing few examples are yet found in environmental science. The multi-disciplinary project SPICOSA used a common, component-based simulation framework for environmental modelling, based on 18 case studies through Europe. The development of high-quality model components with potential for reuse turned out to be a challenge despite of the guidelines and tutorial examples provided. Well-designed components are of appropriate granularity, encapsulated, with a limited use of connectors and proper data handling. Ultimately, the success of a model library depends on a sufficient set of quality components with complementary functionalities, a framework for quality control, and support of the environmental modelling community. Highlights: Component reusability depends on encapsulation, granularity, data handling, and documentation. Model components should be defined at the level of system state variables. Excessive use of connectors reduces the reusability of model components. Component design guidelines should be completed with tutorial examples.